1978
DOI: 10.1152/ajpheart.1978.235.5.h601
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of coronary blood flow and transmural distribution in miniature pigs

Abstract: The relationship between phasic systolic and diastolic coronary blood flow and its transmural distribution has been studied in 29 Yucatan miniature pigs at rest and during heavy exercise, with and without adenosine infusion (1.5 mg . kg-1 . min-1) and with and without a subtotal coronary artery occlusion. Altered factors that affected coronary flow included vascular resistance, perfusion pressure, myocardial oxygen demand, and extra-vascular pressure. The data indicate that, at rest, endomural perfusion is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…39 In addition, nearly identical treadmill exercise-induced increases in blood flow have been observed with simultaneous flow probe (to 321% of resting values) and microsphere (to 315% of resting values) measurements in swine. 40 In our laboratory, we previously observed that the vascular resistance responses to dopamine receptor stimulation were similar when measured with a Doppler coronary flow probe or radioactive microspheres. 33 Finally, we observed in 5 swine that coronary artery blood flow increased from 40Ϯ3 mL/min at rest to 71Ϯ6 mL/min (176Ϯ8% of resting values) during exercise at 3 to 4 km/h, while simultaneous microsphere measurements demonstrated an increase in myocardial blood flow from 1.52Ϯ0.07 mL ⅐ min Ϫ1 ⅐ g Ϫ1 at rest to 2.82Ϯ0.32 mL ⅐ min Ϫ1 ⅐ g Ϫ1 (184Ϯ18% of resting values) (authors' unpublished data, 1998).…”
Section: Myocardial O 2 Extraction During Treadmill Exercisementioning
confidence: 87%
“…39 In addition, nearly identical treadmill exercise-induced increases in blood flow have been observed with simultaneous flow probe (to 321% of resting values) and microsphere (to 315% of resting values) measurements in swine. 40 In our laboratory, we previously observed that the vascular resistance responses to dopamine receptor stimulation were similar when measured with a Doppler coronary flow probe or radioactive microspheres. 33 Finally, we observed in 5 swine that coronary artery blood flow increased from 40Ϯ3 mL/min at rest to 71Ϯ6 mL/min (176Ϯ8% of resting values) during exercise at 3 to 4 km/h, while simultaneous microsphere measurements demonstrated an increase in myocardial blood flow from 1.52Ϯ0.07 mL ⅐ min Ϫ1 ⅐ g Ϫ1 at rest to 2.82Ϯ0.32 mL ⅐ min Ϫ1 ⅐ g Ϫ1 (184Ϯ18% of resting values) (authors' unpublished data, 1998).…”
Section: Myocardial O 2 Extraction During Treadmill Exercisementioning
confidence: 87%
“…The pressure at which endocardial flow begins to decrease is even higher during exercise, which augments MVO 2 , heart rate, and myocardial tissue pressure (47). Despite this recognition, limitations in endocardial flow (i.e., low ENDO/EPI ratios) are not evident in normal hearts under physiologic conditions across a wide range of heart rates and MVO 2 in either the left (53, 122, 606, 642, 752, 825) or right ventricle (39, 48, 606, 739, 1024). Therefore, under normal physiologic conditions the coronary circulation is able to integrate compressive forces and microvascular resistances in a manner that allows for adequate delivery of substrates to all myocardial layers.…”
Section: Extravascular Compression and Transmural Flow Distributionmentioning
confidence: 99%
“…However, transmural microvascular resistance is heterogeneous, with higher minimum resistance (less relaxation) in the subendocardium than the subepicardium. The subendocardium is further disadvantaged by the direction of blood flow, which is from the epicardium to endocardium 50. Furthermore, during exercise the contractile forces within the heart exert pressure on the microvasculature.…”
Section: Physiological Responses To Acute Physical Stress and Anginamentioning
confidence: 99%